К ВОПРОСУ О СООТНОШЕНИИ КОСМОЛОГИИ Л.П. КАРСАВИНА И ПРАВОСЛАВНОЙ ТРАДИЦИИ - МЕЗЕНЦЕВ, Иван Валерьевич; НАДЕИНА, Дарья Александровна (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2024)
This article analyzes the relationship between the cosmology of L.P. Karsavin and the Orthodox dogmatic doctrine of the creation of the world. The authors summarize the opinions of church researchers about Karsavin's cosmology and show how L.P. Karsavin understood his philosophy in the context of the Orthodox tradition. The article concludes that Karsavin's metaphysics is more in line with the mystic-gnostic tradition, rather than Orthodox dogmatics. At the same time, Karsavin's cosmology, like church cosmology, tends to take a middle position between pantheism and dualism.